The Application Of Canvas Business Model And Financial Feasibility Analysis - Hermawan, Francisca; Salamin, Petrus Pius; Putra, Joshua Iskandar (Jurnal Manajemen Bisnis, 2018)
The purpose of this research is to analysis how business model canvas can be applied to photography business, and to know its financial feasibility, especially from the point of view Net Present Value (NPV) and Payback Period.” TAP Studio” is the name of anew photography business, that is a house production, producing video and photography., with total investment amounting to Rp. 150.000.000. The research was conducted in June 2017 - December2017 using data collection techniques such as observation, interviews, and secondary research. It can be concluded that Canvas Business Model can be applied to a photography industry, and its financial feasibility, especially in term of Net Present Value is feasible, because its NPV is positive IDR 491.199.909. Furthermore, the Payback Period is 2 years and 8 months.